AL-LUGHAH AS-SAMIYAH - Mandrasi Amira Sa'idah (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2017)
The so-called “As-Sēmiyyūn” (Semitic) are in fact Arab tribes migrated by natural factors from the Arabian Peninsula in search of water and grassland, and the people that established in this part of Western Asia civilizations are linked linguistically and historically as well as in terms of genealogy. Semitic language means a dialect of language of the inhabitants of the southern part from Western Asia bordered by Jordan in the North and the Arabian Sea in the South, the Gulf of ‘Ajam in the East and the Red Sea in the West. The Semitic language has been known universally for the language of those inhabitants and was used for the first time in the 18th century A.D., while the westerners divided the languages of the world by similarities between those languages to the Arabic, Hebrew, Habashiya, Syriac, Assyrian, Aramaic and other languages. This article aims to learn the Semitic language through division in different ages included the general observation on its history, its characteristics and its division.